Development of Creative Economy Based on Local Wisdom in the Era of Digital Transformation Through Inclusive Education and Village Community Empowerment in Bantul Regency, Yogyakarta - Rahman, Irhamni; Hakim, Lucky Maulana (Universitas Muhammadiyah Jakarta, 2024)
This research aims to examine how inclusive education, community empowerment, and digital transformation contribute to the development of a creative economy based on local wisdom in Indonesia, with a focus on Bantul Regency, Yogyakarta. Inclusive education, which is a primary concern in addressing social inclusion challenges, still shows low participation rates in Indonesia. Meanwhile, the presence of local communities in Indonesia, if supported by local governments and digital transformation, has the potential to open new opportunities in developing the creative economy with the utilization of digital technology to enhance reach and competitiveness. The research methodology employs a case study approach with qualitative methods, allowing for an in-depth understanding of the phenomena under investigation. Data were collected through library research and participant observations and then analyzed thematically. The research findings indicate that collaborative initiatives of local governments with stakeholders to develop locally-based tourism villages and the implementation of inclusive education in schools around these tourism villages have improved social inclusion and empowered the local economy. Active participation from various parties, such as local governments, communities, and social organizations, in managing and promoting tourism destinations has successfully increased collective income and community welfare. Through the adoption of digital technologies such as social media, online marketing, tour guide applications, and data management, tourism villages in Bantul can reach broader markets and enhance their competitiveness. As a result, not only is there an increase in economic welfare for local communities, but also an appreciation for local wisdom and traditional culture.